Endoscopic ultrasound-guided fine-needle aspiration in diagnosing primary medistinal large B-cell lymphoma: a case report - Tang, Jingyan; Guan, Yuchen; Zhang, Jianfeng; Guan, Chengqi (Frontiers in Oncology, 2025)
BackgroundMediastinal tumors present diagnostic challenges due to their unique location. This case report presents a patient diagnosed with primary mediastinal large B-cell lymphoma (PMBCL) using endoscopic ultrasound-guided fine needle aspiration (EUS-FNA), demonstrating the utility of this minimally invasive technique in detecting and confirming PMBCL.Case descriptionA 34-year-old previously healthy woman came to our hospital complaining of dysphagia for 3 months. The gastroscopy showed a huge submucosal bulge in the middle of the esophagus, and a contrast-enhanced computed tomography scan of the chest revealed a left main bronchus nodule measuring 15 mm, mediastinal lymph node enlargement, and fusion with necrosis. Subsequently, we obtained the tissue from the mediastinal mass through EUS-FNA and the tissue from the left main bronchus nodule through transbronchoscope biopsy. According to the pathologic findings, we made a clear diagnosis: primary mediastinal large B-cell lymphoma.ConclusionAs a minimally invasive technique, EUS-FNA is highly safe, repeatable, and accurate for lymphoma diagnosis. Although there are some limitations, it can play an important role in diagnosing mediastinal tumors.